(untitled) (Fiep Bulletin - online, 2011)
Based on the literature that mixed groups permit the positive development of gender relations, the present study aimed to investigate the existence of contributions and limits of a class of Physical Education School composed of manner mixed (boys and girls together) in comparison to classes female and male, with regard to the following variables: relationship with the other sex; concept of students in relation to the capacity of the other sex in the classroom and Physical Education classes; prejudices and gender stereotypes for jokes, activities and partner; preference and way of thinking in relation to the formation of classes of Physical Education based on sex. For both, we performed a case study guided by focus methodological quantitative-qualitative. The sample was composed by 45 students of both genders with mean age 12.8 years, students of a same professor of Physical Education that, despite contrary to the formation of classes mixed, offered to participate in the research forming three different groups: mixed, male and female. The data, collected by means of interview semi structured performed before and after the period of four months of classes, were analyzed using the technique of content analysis. The results indicated that the mixed training presented a favorable trend as regards the development of some of the analyzed variables and indifferent in relation to other, which led us to the conclusion that the formation of mixed groups in physical education classes can shape a rich opportunity the development of gender relations more appropriate. However, the simple junction of boys and girls in the same group does not guarantee the full development of the aspects investigated. New studies need to be carried out with the professionals who defend the co-education with a view to investigate the results of an intervention that goes beyond the simple co-instruction.